Quality appraisal of existing guidelines for the management of headache disorders by the AGREE II’s method - Vaz, Juliana Maria de Albuquerque (2022)
Objective: To evaluate the quality of existing clinical practice guidelines for headache management and their main recommendations. Background: Evidence-based clinical practice guidelines have been developed to support the clinical decision-making. However, to achieve this goal, the quality of these guidelines must be ensured. Methods: A systematic search for clinical practice guidelines for headache management was conducted in the PubMed database, in websites of known guideline developers and in websites of known headache associations. The quality appraisal was performed through the Appraisal of Guidelines for Research and Evaluation II method. Results: Twelve guidelines were evaluated. The domains of rigor of development, applicability, and editorial independence, which most influence the overall quality of guidelines, had the lowest average scores and the highest standard deviation rates (61% 23; 37% 20; 53% 31). The main recommendations regarding medication use for acute treatment of episodic tension-type headache and migraine in adult patients consisted of paracetamol, acetylsalicylic acid, and other nonsteroidal anti-inflammatory drugs in all guidelines. Conclusions: The statistical results indicate that the appraised guidelines have room for both individual and collective improvement. In addition, there is a well-established medication recommendation pattern among all guidelines evaluated.